O y-2x = -5
O -2y = 10x - 4
O 2y = -4x - 10
Q(−5, 8), S(1, −3)
Q(5, −8), S(−1, 3)
Q(−5, −8), S(1, 3)
Q(−5, 8), S(−1, 3)
a. 0
b. 1
c. 9 + 6i
d. -9 + 6i
An equation is formed of two equal expressions. In the given equation (9–6i)×m = 9–6i, the value of m is 1.
An equation is formed when two equal expressions are equated together with the help of an equal sign '='.
In the given equation (9–6i)×m = 9–6i, the value of m can be found as,
(9–6i)×m = 9–6i
Divide both the sides of the equation by (9–6i),
m = 1
Hence, In the given equation (9–6i)×m = 9–6i, the value of m is 1.
Learn more about Equation:
#SPJ2